Ma Mère LOye: os des (limites) da interpretação - Debora Batista Baiao (2005)
This work presents a study on what is Interpretation and focuses on MaMère LOye, piece by the French composer Maurice Ravel, through which there will be a search for an interlocution with apparently extramusical elements, discussing the artistic and cultural universe from that time as well as the symbolist poets ideas. So as to follow this purpose, three topics are considered essential to address Ma Mère LOye: the understanding of the concept of art based on a language which is suggestive, spiritual, filled with musical effects and which is elaboratedafter meticulous planning; the study and signification of fairy tales as a literary style in this scenery and; at last, the analysis of Ravels piece not only focusing on elements related to its musical building, but, also observing it trough an imaginative and literary view, combined with ideas expressed in specific texts by Charles Baudelaire and Edgar Allan Poe.